TRANSPARENCY OF DIRECT CASH ASSISTANCE (BLT) RECEIPT SERVICES IN BONE KAINSETALA VILLAGE, BONE DISTRICT, MUNA REGENCY - Abdullah, Abdullah; Nur Achmad, Farid Yusuf; Mayunita, Sry (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
The purpose of this study is to determine the implementation of Transparency of Direct Cash Assistance (BLT) Receipt Services to the people of Bone Kainsetala Village, Bone District, Muna Regency. This type of research is a type of qualitative research where this method can also be used to gain insight into something that is just a little known, and can help researchers provide complex details about phenomena that are difficult to reveal. The results of this study show that the implementation of transparency and accountability in the BLT program in Bone Kainsetala Village has been implemented quite well in accordance with the indicators The implementation of transparency in Bone Kainsetala Village has been implemented and implemented quite well but not optimally. The Village Government has tried to provide information and be open regarding the distribution of direct cash assistance by utilizing social media such as Facebook, whatsApp, and also providing information boards for people who do not have social media.